Strategy to Improve Intelligent Characters and the Fighting Ability for Junior Athletes of Tarung Derajat - Alnedral,; Umar,; Aldani, Nissa (International Journal of Psychosocial Rehabilitation, 2020)
The main issue of this study is that the learning outcomes are still low, especially in intelligent character and fighting ability mastery. This research aims to determine the intelligent character and fighting ability mastery of Tarung Derajat Junior athletes at the level of Kurata III and IV (age groups of 10-12 years old and 13-14 years old) that implemented the BMB3 learning strategy. This study was an experimental study with a one-group pretest-posttest design. This study involved 30 athletes of the PLN training unit in Pariaman chosen by stratified-cluster random sampling. The instrument used to collect the data was a questionnaire of intelligent character and fighting ability tests. The data were analyzed using descriptive statistics for the reveal of training conditions, and then the hypothesis was tested using t-test analysis. This study revealed that there was an improvement in intelligent character mastery and the fighting ability of athletes in Kurata III and IV.